Investigating the Effect of Nozzle Diameter on Tensile Strength in 3D-Printed Printed Polylactic Acid Parts - Kartal, Fuat; Kaptan, Arslan (Black Sea Journal of Engineering and Science, 2023)
Three-dimensional (3D) printing is a rapidly evolving manufacturing technology that enables the production of intricate, customizable parts with a wide range of applications. The quality and mechanical properties of printed parts are heavily influenced by the process parameters, such as nozzle size. This study presents a comprehensive investigation of the effect of nozzle diameter on the tensile strength of 3D-printed polylactic acid (PLA) parts, focusing on six nozzle sizes: 0.3, 0.4, 0.5, 0.6, 0.7, and 0.8 mm. PLA, a commonly used thermoplastic in 3D printing, was employed as the material of choice. Using an open-source Fused Filament Fabrication (FFF) 3D printer, dog bone-shaped specimens were printed according to the ASTM D638-Type IV standard for tensile testing. The results reveal a strong correlation between nozzle size and tensile strength, with smaller nozzles producing parts with higher tensile strength due to finer layers and improved interlayer adhesion. However, the trade-off between tensile strength and printing time associated with smaller nozzle sizes must be considered when optimizing the 3D printing process for specific applications. This study provides essential insights into the influence of nozzle diameter on tensile strength, offering valuable guidance for achieving desired mechanical properties in 3D-printed parts.
Keywords: Engineering; D printing; Fused filament fabrication; Nozzle diameter; Tensile strength; Polylactic acid; Additive manufacturing; Mühendislik